Talent Management - A Strategic Tool for Sustainable Human Resource Management with Special Reference to ITES Sector - Suma (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Most of the organization give more vital for talented employees as it is more competitive advantage in the market with creating opportunity with the talent employees in their system and to endure in the cutthroat world of business. Simultaneously the organization aware of the talented employee to get success in the present era and stay alive in the argumentative business environment. Talent management is solitary of the significantly essential need and handled appropriately in direction to accomplish the best results. Businesses realize that in order to get the greatest outcomes, they must both engage exceptional individuals and provide them with incentives to stay with the company. As a result, it is evident that handling talent properly is crucial. Nowadays, talent management advancement is seen as the most important component of company and as exclusive of the main obstacles to long-term competitive reward in companies. The research explores the study of talent management towards sustainability of human resources based on the demographical factors and its intensity in the ITES sector in Bangalore. The population of this study encompasses ITES employees working in Bangalore city and the sample consists of ITES companies of Bangalore city. The data was collected by using structured questionnaire with 118 IT employee. The objective of the study is to understand the talent management is a strategic tool for sustainable human resources at ITES Bangalore city. Aims: The aim of the study is to understand the talents and its importance in the organization for growth with the effective understanding and utilization of demographical factors in a better way for the sustainable human resources in the ITES sector, Bangalore. Research Design: Structured questionnaire method was used to collect the data and the nominal scale and ordinal scale used to quantify the items within the questionnaire. The sample size of the study was 138 workers working in IT & ITES companies, Bangalore. IBM SPSS 20 version software helped to examine the data by adopting various statistical tools to assess the hypothesis, such as T Test, Correlation, Chi-square test. Results: Granting to the study, there is a connection between Talent Management and sustainability the long-term viability of human resources using demographic factors in a major role. Moreover, the study demonstrated how talent management promote sustainability of human resources as a strategic tool among IT & ITEs sector.